Lavender And Lemon Aromatherapy Against Anxiety III Trimester Pregnant Women Facing Labor - Asnita Asnita; Wasis Pujiati; Komala Sari; Meily Nirnasari (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Management of anxiety can be done pharmacologically and non-pharmacologically, non-pharmacologically, one of which is aromatherapy. This study aims to determine the Comparison of Lavender and Lemon Aromatherapy to the Anxiety of Trimester Pregnant Women Facing Childbirth. This type of research is a Quasi Experiment with the design of a method of two groups, pre and post-test without control. In a sample of 22 respondents, the sampling technique is quota sampling. The research instrument used Zung Self-Rating Anxiety Scale (ZSAS) sheets—data analysis using the Wilcoxon and Mann-Whitney tests. Based on the results of the Wilcoxon test, the lavender and lemon aromatherapy group showed a p-value of 0.000 (<0.05). The results of the Mann-Whitney test analysis found that lavender aromatherapy was more effective than lemon, with a p-value of 0.672. It can be concluded that there is no significant comparison of lavender and lemon aromatherapy to the anxiety of pregnant women in the third trimester facing childbirth. Third-trimester pregnant women facing labour who experience anxiety can use lavender and lemon aromatherapy to reduce stress.